An analysis of 300 intravenous pyelographs - Kenanoğlu, Abdullah; Müftü, Yunus (The Turkish Journal of Pediatrics, 1962)
In addition to the simplicity, safety and value of intravenous pyelography as a diagnostic tool it is an important procedure in Turkey for revealing urinary calculi (our most frequent urinary pathology) the calix deformities and such complications as hydronephrosis and pyelonephritis. It is also invaluable in indicating necessary surgical treatment.